Reasons for Non-Compliance to Inhaled Medications among Adult Asthma Patients Attending Referral Chest Hospital in North India - Dar, Mohd Yousoof; Shah, Naveed Nazir (International Journal of Innovative Research in Medical Science, 2018)
Introduction: Asthma is a major public health problem affecting a large number of individuals of all ages, characterized bychronic airway inflammation and inhaled medications are main stay of treatment but compliance to these medications is poor.Aim: This study was conducted to look for common reasons for non-compliance to inhaled medications (MDI and DPI) in asthmapatients attending out-patient department of a referral chest hospital. Material and methods: The study was conducted on 150diagnosed asthma patients on follow based on an open labeled questionnaire in a hospital from North India. Results: Overallcompliance of the patients to inhaled medications (MDI and DPI) was only 34.6% (52 /150 patients) and 65.4 % (98 out of 150) were found to be noncompliant. Among reason for non-compliance, belief that medications were not needed during symptom freeperiod was found in 43.8% (43/98), followed by feeling that they may become dependent/ develop addiction if used for long timein 32.6% (32/98) and social embarrassment in using inhalers found in 14.2%(14/98). All other reasons accounted for onlyaround 9% of non-compliance. Conclusion: The data indicates that despite strict instructions for adherence to medicationcompliance rate was poor, although majority of the patients believed that compliance was extremely important. This studysuggests that besides continued health education new health care initiatives are needed to be designed to improve the complianceof asthma patient for inhaled medications.